The Role of Syi'ah Hadith in the Tarekat Syattariyah of Abu Peulekung in Aceh, Indonesia - Yahya, Faisal; Mubarrak , Husni; Mustaqim, Riza Afrian; Abdullah, Arifin (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2025)
This study explores the role of Syi'ah hadith in the Tarekat Syattariyah, particularly in the context of the Abu Peulekung community in Aceh, Indonesia. The Tarekat Syattariyah is one of the most prominent Sufi orders in Southeast Asia, known for its unique spiritual practices and teachings, which blend elements of both Sunni and Shia traditions. This research examines how Syi'ah hadith is integrated into the teachings and practices of the order, and how it influences the spiritual lives of its followers. The Abu Peulekung community, located in Aceh, has long been a center for the practice of Tarekat Syattariyah, with a strong emphasis on the teachings of Sufi saints. The use of Syi'ah hadith in this community is notable for its distinct emphasis on the spiritual dimensions of Islamic teachings, particularly in the context of love for the Prophet and his family, which aligns with Shia principles. Through a detailed examination of the hadiths used by the followers of this order, this study highlights the living tradition of Syi'ah hadith in a predominantly Sunni region. It also sheds light on how these hadiths contribute to the development of religious identity, spiritual practices, and inter-sectarian relationships in Aceh. The findings contribute to the broader understanding of the diversity of Islamic traditions in Southeast Asia